THE ROLE OF TOPOGRAPHY AND PHOTOGRAMMETRY IN CONNECTING ARCHAEOLOGICAL VESTIGES. DOCUMENTING THE THERMAE OF LEGIO XIII GEMINA FROM APULUM - Ionuț MAICAN; Anca TIMOFAN; Cristian FLORESCU; Călin ȘUTEU; Constantin-Irinel GREȘIȚĂ (Journal of Ancient History and Archaeology)
The archaeological research, especially the preventive type, is usually determined by interventions and investments in a specific archaeological area, having also a powerful destructive character. The role of the topography in this research, together with the legal compulsory character, is very important; the modern measuring techniques have a special contribution in the contextualisation of the archaeological discoveries, especially for those from a documented archaeological area, due to the fact that it can be a revealing factor by bringing vestiges together and achieving a “composite” material, that can be useful to draw important conclusions related to the ”monolithic” ensemble of structures and buildings belonging to the same period. At the same time, the modern techniques for the collection, storage and analysis of the topographic-archaeological data may be significantly important for the sustainable development of a region, by preserving and highlighting the cultural heritage.